I WILL GIVE BRAINLIEST!!
![I WILL GIVE BRAINLIEST class=](https://us-static.z-dn.net/files/df3/af3f00bfc4d8e37f147ddc5c530e3319.png)
Answer:
[tex]\text{D. The terms may be combined.}[/tex]
Step-by-step explanation:
Recall that [tex]\sqrt{a\cdot b}=\sqrt{a}\cdot\sqrt{b}[/tex]. Using this, we can simplify and combine the two terms:
[tex]6\sqrt{32}-12\sqrt{72},\\=6\cdot \sqrt{4}\cdot \sqrt{8}-12\cdot \sqrt{9}\cdot \sqrt{8},\\=6\cdot 2\cdot \sqrt{8}-12\cdot 3\cdot \sqrt{8},\\=12\sqrt{8}-36\sqrt{8},\\=-24\sqrt{8}=-24\cdot\sqrt{4}\cdot\sqrt{2}=\boxed{-48\sqrt{2}}[/tex]. Therefore, the terms may be combined.